Need help in Homogeneous equation ...

Hi.

first i apologize for my bad english.

I need to solve this equation : ( i have its solution but can't understand some parts of it )

**(y**^{4} - 3x^{2})dy + xydx = 0 (1)

I use **y = t**^{a} ــ> **dy = at**^{a-1}dt (2) and place it in (1) :

**a(t**^{5a-1} - 3x^{2}t^{a-1})dt + xt^{a}dx = 0

then i don't understand this next part ( I'm typing it from solution of problem ): **5a - 1 = 2 + a - 1 ?**

it then calculates a = 1/2 and solves the equation ... i don't get why 5a - 1 = 2 + a - 1 ...

thanks in advance.

Re: Need help in Homogeneous equation ...

Hey mhmarefat.

Is this a Bernoulli type DE?